قياس أثر بعض مؤشرات السياسة الاقتصادية الكلية على معدلات الفقر في الجزائر للفترة: (1990-2019) - سعاد, فنيك; مبروكة, عقاب; فاطمة, بودوخة (جامعة الوادي university eloued, 2020)
This study aims to study the impact of some macroeconomic policy indicators on poverty rates through a standard study of the case of Algeria during the period from 1990-2019. In order to achieve the goal of this study, the theoretical aspect of the phenomenon of poverty, its concept, causes, methods of measurement and its indicators was reviewed. The study also dealt with the presentation of the development path of the most important macroeconomic policy indictors in Algeria during the period between 1990-2019 (fiscal policy index, economic growth rate, monetary policy index, Unemployment rate, external equilibrium index), and the relationship between them. To achieve this, an ARDL model was used. The study also concluded that there is a long-term equilibrium relationship between the poverty rate and the rest of the targeted macroeconomic policy indicators. Its helps decision-makers to formulate other economic policies that contribute to reducing poverty. تهدف هذه الدراسة إلى دراسة أثر بعض مؤشرات السياسة الاقتصادية الكلية على معدلات الفقر من خلال دراسة قياسية لحالة الجزائر خلال الفترة الممتدة من 1990-2019. ولتحقيق هدف هذه الدراسة تم استعراض الجانب النظري للفقر، مفهومه، أسبابه، طرق قياسه ومؤشراته، كما تناولت الدارسة عرض مسار تطور أهم مؤشرات السياسة الاقتصادية الكلية في الجزائر خلال الفترة الممتدة مابين 1990-2019 (مؤشر السياسة المالية، معدل النمو الاقتصادي، مؤشر السياسة النقدية، معدل البطالة، مؤشر التوازن الخارجي)، والعلاقة بينهما. ولتحقيق ذلك تم استخدام نموذج الإنحدار الذاتي للإبطاء الزمني الموزع (ARDL). كما خلصت الدراسة إلى وجود علاقة توازنية طويلة الأجل بين معدل الفقر وباقي مؤشرات السياسة الاقتصادية الكلية المستهدفة في الدراسة.حيث تساعد أصحاب القرار على رسم سياسات اقتصادية أخرى تساهم في الحد من الفقر
مذكرة ماستر اقتصاد كمي
Keywords: قياس ، مؤشرات ،السياسة الاقتصادية ،الكلية ، معدل الفقر، الجزائر; Poverty rate, macroeconomic policy indicators, bounds test, ARDL model.